1960
DOI: 10.1152/ajplegacy.1960.199.3.579
|View full text |Cite
|
Sign up to set email alerts
|

Maximal acid secretory response to histamine and its relation to parietal cell mass in the dog

Abstract: Gastric secretion in response to graded doses of histamine was obtained from the whole stomach in five trained dogs, and the animals were sacrificed to determine the total number of parietal cells in the stomach. Histamine was administered by single s.c. injection (Hsc) and continuous i.v. infusion (Hiv). Maximal histamine response (MHR) was determined, and studies permitting the construction of dose-response curves were carried out in three of the five dogs. Dose-response curves for acidity and for acid outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

1964
1964
1989
1989

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(24 citation statements)
references
References 0 publications
1
21
0
2
Order By: Relevance
“…The present study thus emphasizes the importance of considering the tone of both parts of the autonomic nervous system when studying gastric secretion even when induced by peripherally acting stimu lants. The remark of Marks et al [5] that the pepsin output is a better parameter of the tone in the autonomic nervous system than volume or acid output, is confirmed by our data after a single shot as well as by Hirschowitz [3] during continuous infusion.…”
Section: Discussionsupporting
confidence: 88%
“…The present study thus emphasizes the importance of considering the tone of both parts of the autonomic nervous system when studying gastric secretion even when induced by peripherally acting stimu lants. The remark of Marks et al [5] that the pepsin output is a better parameter of the tone in the autonomic nervous system than volume or acid output, is confirmed by our data after a single shot as well as by Hirschowitz [3] during continuous infusion.…”
Section: Discussionsupporting
confidence: 88%
“…Marks, Komarov, and Shay (1960) (Morton and Stravraky, 1949) and it is possible that at critical levels of Urecholine dosage the addition of gastrin or histamine causes reversal of effects on pepsin but not on acid secretion.…”
Section: Methodsmentioning
confidence: 99%
“…In experimental animals such as dogs, on the other hand, the acid secre tion continues to increase up to an intravenous histamine dose of 96-144 ¡xg/ kg/h [18], and 125 ¡xg/kg/h [11]. H ir sc h o w it z [12] has suggested that the observed inhibition [6,18] of acid secretion with very high doses may be an artifact of the experimental technique related to the decline in acid produc tion with time.…”
Section: Introductionmentioning
confidence: 99%